Certification of amburana in the aging of cachaça (Research, Society and Development, 2020)
Cachaça is defined as sugarcane spirit produced in Brazil, but it still lacks references that valorize the aging in native woods. Amburana (Amburana cearensis) is a Brazilian tree widely used in making casks for storing cachaça. Among its phenolic derivatives, coumarin stands out. Its content is determinant in the sensorial characteristics developed in the beverage during the aging process. We propose a simple and rapid method (15 min) that allows the certification of the storage of cachaça in amburana barrels and the determination of the coumarin content. Using high-performance liquid chromatography, the identity of the wood is attested by the peculiarities of the chromatographic profile obtained with a UV detector (274 nm) in an isothermal environment (40 oC). Coumarin was easily identified among the peaks obtained, and it could be quantified using a standard curve.